Oral rehabilitation of a patient with temporomandibular joint ankylosis caused by ankylosing spondylitis: A case report - Brkić, Zlata Ilija; Pijevčević, Nikola Bogosav; Pavlić, Verica; Petronijević, Milan (Vojnosanitetski pregled, 2017)
Introduction. Ankylosing spondylitis (AS)/Morbus Bechterew is a chronic inflammatory rheumatoid disease. The temporomandibular joint (TMJ) dysfunction is involved in 4–35% of AS cases, and is correlated to the severity and extension of AS. Even though AS-caused TMJ ankylosis is exceptional, one should have high index of suspicion of TMJ ankylosis in AS for an early detection, because it is an extremely serious and disabling condition that causes problems with mastication, swallowing, digestion, speech, appearance and poor oral hygiene with heavy caries. Case report. A 54-year-old male patient sought medical attention at the Department of Periodontology and Oral Medicine, Clinic for Dentistry at the Military Medical Academy, Belgrade, Serbia, with the chief complaint of pain in the area of the upper left canine in the presence of limited mouth opening. The treatment plan consisted of upper left canine management and rehabilitation of the remaining teeth in the frontal and the premolar region in both, the upper and lower jaw. Even though molar region needed to be treated, unfortunately it was not in the treatment plan because ankylosis of TMJ made the treatment impossible. Conclusion. The patients with AS-caused TMJ ankylosis are considered a diagnostic challenge to routine dentistry. Accent should be given to early diagnosis and multidisciplinary approach in the treatment of the AS patients towards the favorable disease course and outcome.
Keywords: spondilitis; ankylosing; temporomandibular joint; ankylosis; diagnosis; dental care for chronically ill; treatment outcome